2001
DOI: 10.1007/pl00007547
|View full text |Cite
|
Sign up to set email alerts
|

A follow-up study of 45 patients with elective mutism

Abstract: Forty five patients (23 boys and 22 girls) with elective mutism (8.7 +/- 3.6 years old), who were referred to a university department and a child guidance clinic within a 15-year-period, were followed up on average 12 years later. For 41 of them, sufficient information could be obtained at follow-up, and 31 patients could be investigated personally. At follow-up, an interview and a standardized psychopathological examination were carried out as well as two standardized biographic inventories. The main results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
1
15

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(143 citation statements)
references
References 18 publications
3
124
1
15
Order By: Relevance
“…This is in line with previous studies indicating that intraindividual factors predict the course of SM: Steinhausen et al [34] identified a more extended context of mute behavior, particularly towards peers, as the sole predictor of a poor symptomatic outcome of SM. Remschmidt et al [35] found mute behavior of the child within the core family to be the strongest predictor of a chronic course. Specific speaking patterns might either reflect or result in social withdrawal and thus impact the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous studies indicating that intraindividual factors predict the course of SM: Steinhausen et al [34] identified a more extended context of mute behavior, particularly towards peers, as the sole predictor of a poor symptomatic outcome of SM. Remschmidt et al [35] found mute behavior of the child within the core family to be the strongest predictor of a chronic course. Specific speaking patterns might either reflect or result in social withdrawal and thus impact the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this early onset, children are not commonly referred for clinical assessment until they are between approximately 6.5 to 9 years of age (Ford et al 1998;Kumpulainen et al 1998;Standart and Le Couteur 2003). SM may persist for a few months to several years, and adults diagnosed with SM as children often continue to suffer with social anxiety and deficits in social communication, in addition to displaying other problems with socioemotional and daily adjustment (Remschmidt et al 2001). Despite being diagnostically well-documented (Dummit et al 1997;Kopp and Gillberg 1997;Sharp et al 2007), the etiology of SM remains equivocal.…”
mentioning
confidence: 99%
“…Multiple studies have found links between children with SM and first-order relatives. For example, Remschmidt and colleagues [20] found significant concordance rates of mutism in first-order relatives of children with SM (mothers, 18%; fathers, 9%; siblings, 18%). Additional support for familial vulnerability to anxiety exists in other studies.…”
Section: Parental Psychopathologymentioning
confidence: 99%